RESPON PERTUMBUHAN DAN PRODUKSIJAGUNGMANIS (Zea mays var. saccharataSturt)TERHADAP LIMBAH PADAT PABRIK KELAPA SAWIT DAN NPK - Sitepu, Arjunius; Adiwirman, Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to examine the density of solid waste of palm oil factory and NPK and get the dose of fertilizer that gives growth and yield of sweet corn plant. This research has been conducted at Experimental Garden of Agriculture Faculty of University of Riau, Campus of Bina Widya km 12,5 Simpang Baru Village, Tampan Sub District, Pekanbaru. This research has been conducted for three months from September until November 2016. This research was conducted experimentally using factorial randomized block design (RAK). The first factor consisted of 4 levels (LPPKS 0 ton / ha, LPKKS 10 tons / ha, LPPKS 20 tons / ha and LPPKS 30 tons / ha) and the second factor consisted of 2 levels (NPK 150 kg / ha, NPK 300 kg / ha ). The observed parameters of plant height, number of leaves, stem diameter, diameter, length and cobs are weightless and not weighted, the production per m2, the number of seed lines, the number of seeds per line and the sugar content in the seeds. The result of variance is significantly different then continued by using BNJ test at the 5 % level. The results concluded that NPK treatment increased sweet corn yield. Production per m2 was positively correlated with all observation variables except for observed sugar levels in seeds that were negatively correlated. Keywords: Sweet Corn, LPPKS, NPK